(3aJM GdPNGFQ hGdCZdGb TQM JQLeGf GdCThGbs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3CSJNQJ Gddg JYGdi, hbjOJ aj gPg GdChQGb eG fXeJg ef GdCHjGJ GdZRdjI HecI GdecQeI TQagG Gddg JYGdi s
(3BNQgG (B:s
(3GdWjH ef QjM GdWjH HfaMJgG gPG BNQg s
(3GfXQ GdLRA GdChds
(3GdbSe GdKGfj GdQbe (B1146 (3COH hgj TQM GdOjhGfs
(3HChdgG JedcGf HJGQjN (B1126(3g`s
(3hJedc BNQ HJGQjN (B1197(3g`s
(3hJMHjS SfI (B1232(3g` s
(3gh TQM OjhGfg GdeSei H` (B"(3JQLeGf GdCThGb(B" (3hGdCKfGf dg s
Keywords: (3GdCOHs